Sleep disorder diagnosis: The design and implications of online tools - Jacqueline Blake; Don Kerr (Decision Analytics, 2014)
Sleep disorders are a significant and growing problem, both for the economy of the nation and for the physical and psychological well-being of individual sufferers. The purpose of this research was to investigate the operational, administrative and medical environment within which sleep physicians currently diagnose patients with sleep disorders and develop an online support system that would more efficiently gather patient history data, and so improve the effectiveness of patient-physician consultations, the diagnoses, and patients' self-management of any subsequent treatment plans. The development of the online tools used a design science approach and those tools evaluated for usefulness and ease of use by physicians and the general population. The physicians found that the patient history information was in a form that facilitated assimilation with the removal of routine data collection allowing a more targeted or shorter consultation. The users found the application easy to use and that it made them think about their sleep quality. The implications for future practice of sleep disorder diagnosis and the value of the collection of patient history which would be available for analysis is also discussed.
Keywords: 330; Health informatics; Chronic condition; Sleep disorders; Evidence base; Decision analytics